2017
DOI: 10.3390/ma10090983
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effectiveness of Microspheres Based on Silk Sericin and Chlorella vulgaris or Arthrospira platensis for Wound Healing Applications

Abstract: Some natural compounds have recently been widely employed in wound healing applications due to their biological properties. One such compound is sericin, which is produced by Bombix mori, while active polyphenols, polysaccharides and proteins are synthetized by Chlorella vulgaris and Arthrospira platensis microalgae. Our hypothesis was that sericin, as an optimal bioactive polymeric carrier for microencapsulation process, could also improve the regenerative effect of the microalgae. A solvent-free extraction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…The rise in scavenging of free radicals could be attributed to an increase in pigment [32] and polysaccharide [36,37] content, which plays an important role in the protection of the body's cells and molecules from oxidative stress and in cancer chemoprevention. For example, Chlorella species are known to contain several types of polysaccharides, including β-1,3-glucan, an active free-radical scavenger [38]. In addition, many previous studies found that Isochrysis galbana was rich in polysaccharides, with content up to 25% (dry cell weight) [36].…”
Section: Antioxidant Properties Of Fish Burgersmentioning
confidence: 99%
“…The rise in scavenging of free radicals could be attributed to an increase in pigment [32] and polysaccharide [36,37] content, which plays an important role in the protection of the body's cells and molecules from oxidative stress and in cancer chemoprevention. For example, Chlorella species are known to contain several types of polysaccharides, including β-1,3-glucan, an active free-radical scavenger [38]. In addition, many previous studies found that Isochrysis galbana was rich in polysaccharides, with content up to 25% (dry cell weight) [36].…”
Section: Antioxidant Properties Of Fish Burgersmentioning
confidence: 99%
“…They also showed that sericin microspheres loaded with tumor necrosis factor-α (TNF-α) blockers contribute to the down-regulation of cytokines [ 10 ]. In addition, a great deal of research on sericin and silk fibroin-based biomaterials, including the use of silk fibroin microspheres as a promoting wound healing material or a local coagulant [ 11 , 12 , 13 ], and sericin as a natural carrier for drug delivery, has been documented [ 14 , 15 , 16 ]. However, sericin contains a large amount of random coil structures, resulting in the formation of amorphous and brittle sericin materials which are not suitable for biomaterial application [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a limited number of studies reporting the promigratory and wound healing effects of Chlorella sp. extracts in vitro and in vivo [29][30][31]. Chlorella vulgaris dressing promoted wound closure and minimized the formation of scar tissue during the healing process compared to the control wounds created on the dorsal surface of rats [29].…”
Section: The Effect Of Water and Ethanolic Extracts Of The Microalga mentioning
confidence: 99%
“…had beneficial effects on skin lesions in mice [30]. The wound healing potential of Arthrospira (Spirulina) platensis extract has also been compared to the wound healing potential of Chlorella vulgaris extract using human fibroblasts as a cellular model [31]. It has been concluded that Arthrospira extract stimulated wound closure more efficiently than Chlorella extract [31].…”
Section: The Effect Of Water and Ethanolic Extracts Of The Microalga mentioning
confidence: 99%